Falls Prevention in Community-dwelling Elderly in Brazil: Strategies and Difficulties in Primary Health Care (Acta Scientiarum. Health Sciences, 2024)
The ageing world population has inspired the current care model to incorporate health promotion. The health of the elderly within primary health care aims to maintain functionality in old age. Thus, the prevention of falls by the elderly ensures health promotion by preventing various damages and health problems. Though, effective preventive action is a complex task that health workers have to face. It aims to highlight the difficulties encountered and describe the strategies used to achieve health promotion in the elderly to prevent falls. This is a qualitative research with Hegelian dialectics based on the methodological approach. The Focus group technique was made with community health agents from a municipality in the state of São Paulo, Brazil. The Content Thematic Analysis was used to process verbal discourses and retrieve in its entirety factors from data to classify and categorize all aspects of fall prevention. Findings point to difficulties related to the personal beliefs of the elderly, the difficulty of adapting to daily activities, and deficiencies in social support. Among the strategies adopted were multi-professional teams, family and social networks, and longitudinal approaches. The elements and factors described should be incorporated into primary care by health professionals, especially the nurse as a care manager, to encourage protective attitudes, behaviours, and activities with the elderly to maintain healthy ageing. Any related aspect can be partially or totally generalized, in different socioeconomic statuses, because they reflect daily life and potentially explain the incidence of falls under multidimensional issues.